Contribution of thermal expansion and "diffusive" modes to isobaric thermal conductivity of rare gas solids - Pursky, O.I.; Konstantinov, V.A. (Condensed Matter Physics, 2007)
A theoretical model is developed to describe the experimental results obtained for the isobaric thermal conductivity of rare gas solids (RGS). The isobaric thermal conductivity of RGS has been analysed within Debye approximation with regard to the effect of thermal expansion. The suggested model takes into consideration the fact that thermal conductivity is determined by U-processes while above the phonon mobility edge it is determined by “diffusive” modes migrating randomly from site to site. The mobility edge ω₀ is determined from the condition that the phonon mean-free path restricted by the U-processes cannot be smaller than half of the phonon wavelength.